Knockdown of ?2c-Adrenoceptors in the Occipital Cortex Rescued Long-Term Potentiation in Hidden Prenatally Malnourished Rats - Hernandez-Kunstmann, A; Laurido-Fuenzalida, C; Saez-Briones, P (2012)
Moderate reduction in the protein content of the mother s diet calorically compensated by carbohydrates (the so-called "hidden" prenatal malnutrition) leads to increased neocortical expression of the ?2C-adrenoceptor subtype, together with decreased cortical release of noradrenaline and impaired long-term potentiation (LTP) and visuospatial memory performance during the rat postnatal life. ín order to study whether overexpression of the ?2C-adrenoceptor subtype is causally related to the decreased indices of neocortical plasticity found in prenatally malnourished rats, we evaluated the effect of intracortical (occipital cortex) administration of an antisense oligodeoxynucleotide (ODN) raised against the ?2C-adrenoceptor mRNA on the LTP elicited in vivo in the occipital cortex of hidden prenatally malnourished rats. In addition, we compare the effect of the antisense ODN to that produced by systemical administration of the subtype-nonselective ?2-adrenoceptor antagonist atipamezole. Prenatal protein malnutrition led to impaired occipital cortex LTP together with increased expression of ?2C-adrenoceptors (about twice Bmax) in the same cortical region. [3H]-rauwolscine binding assay showed that a 7-day intracortical antisense ODN treatment in the malnourished rats resulted in 50% knockdown of ?2C-adrenoceptor expression and, in addition, completely rescued the ability of the occipital cortex to develop and maintain long-term potentiation. Atipamezole (0.3mg/kg i.p.) also led to full recovery of neocortical LTP in malnourished rats. The present results argue in favor of our original hypothesis that the deleterious effect of prenatal malnutrition on neocortical plasticity in the adult progeny is in part consequence of increased neocortical ?2C-adrenoceptor expression. This receptor subtype is known to be involved in the presynaptic control of noradrenaline release from central neurons, a neurotransmitter that critically influences LTP and memory formation. © 2012 Elsevier Inc.